Enhancement of Food and Nutritional Security of Rural Poor through Tuber Crops - Pradhan, Aliza; Panda, A K; Maske, Mahesh; Bhavani, R V (JOURNAL OF ROOT CROPS, 2017)
The significance of tuber crops as a source of food, nutrition and income for farmers is well known; but these are often overlooked in the debate about improving food security and tackling malnutrition. This study is a sub-component of a Farming System for Nutrition (FSN) underway in Koraput, Odisha and Wardha in the Vidarbha region of Maharashtra, under the research programme on Leveraging Agriculture for Nutrition in South Asia (LANSA). Tuber crops occupy an integral part of the food and agricultural system of communities in these regions but the area under cultivation is very less and it is done in a traditional method. The overall aim was to promote and create awareness of nutrition sensitive agriculture among the tribal poor through introduction of nutrient rich crop varieties both at field and in nutrition gardens followed by their upscale. The study was based on a detailed report of the baseline survey revealing prevalence of anaemia and vitamin A deficiency in these regions. In this context, the study focused on leveraging agriculture for nutrition through a farming system intervention where we introduced orange-fleshed sweet potato ( Ipomoea batatas L.) (rich in Pro vitamin A) instead of traditional cultivar (white fleshed) in the fields as well as in backyard nutrition gardens. The results of this study will help in the preliminary assessment of a nutrient rich sweet potato variety, its preference for adoption among farmers and as a source to address vitamin A deficiency in the country.